UV completion of extradimensional Yang-Mills theory for Gauge-Higgs unification - Pastor-Gutiérrez, Álvaro; Yamada, Masatoshi (Arxiv, 2022)
The $SU(N)$ Yang-Mills theory in $\mathbb R^4× S^1$ spacetime is studied as a simple toy model of Gauge-Higgs unification. The theory is perturbatively nonrenormalizable but could be formulated as an asymptotically safe theory, namely a nonperturbatively renormalizable theory. We study the fixed point structure of the Yang-Mills theory in $\mathbb R^4× S^1$ by using the functional renormalization group in the background field approximation. We derive the functional flow equations for the gauge coupling and the background gauge-field potential. There exists a nontrivial fixed point for both couplings at finite compactification radii. At the fixed point, gauge coupling and vacuum energy are both relevant. The renormalization group flow of the gauge coupling describes the smooth transition between the ultraviolet asymptotically safe regime and the strong interacting infrared limit.
Version 1 vom 26. Mai 2022, Version 3 vom 30. Juli 2022
Gesehen am 17.10.2022